Quantitative Determination of Δ9-THC, CBG, CBD, Their Acid Precursors and Five Other Neutral Cannabinoids by UHPLC-UV-MS - Wang, Yan-Hong; Avula, Bharathi; ElSohly, Mahmoud A.; Radwan, Mohamed M.; Wang, Mei; Wanas, Amira S.; Mehmedic, Zlatko; Khan, Ikhlas A. (Planta Medica, 2018)
Cannabinoids are a group of terpenophenolic compounds in the medicinal plant Cannabis sativa (Cannabaceae family). Cannabigerolic acid, Δ9-tetrahydrocannabinolic acid A, cannabidiolic acid, Δ9-tetrahydrocannabinol, cannabigerol, cannabidiol, cannabichromene, and tetrahydrocannabivarin are major metabolites in the classification of different strains of C. sativa. Degradation or artifact cannabinoids cannabinol, cannabicyclol, and Δ8-tetrahydrocannabinol are formed under the influence of heat and light during processing and storage of the plant sample. An ultrahigh-performance liquid chromatographic method coupled with photodiode array and single quadruple mass spectrometry detectors was developed and validated for quantitative determination of 11 cannabinoids in different C. sativa samples. Compounds 1 – 11 were baseline separated with an acetonitrile (with 0.05% formic acid) and water (with 0.05% formic acid) gradient at a flow rate of 0.25 mL/min on a Waters Cortec UPLC C18 column (100 mm × 2.1 mm I. D., 1.6 µm). The limits of detection and limits of quantitation of the 11 cannabinoids were below 0.2 and 0.5 µg/mL, respectively. The relative standard deviation for the precision test was below 2.4%. A mixture of acetonitrile and methanol (80 : 20, v/v) was proven to be the best solvent system for the sample preparation. The recovery of all analytes was in the range of 97 – 105%. A total of 32 Cannabis samples including hashish, leaves, and flower buds were analyzed.
Keywords: Cannabis sativa; Cannabaceae; cannabinoids; tetrahydrocannabinol; cannabidiol; tetrahydrocannabinolic acid; UHPLC-UV-MS